Mainstreaming Open Textbooks: Educator Perspectives on the Impact of OpenStax College Open Textbookss - Pitt, Rebecca (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
This paper presents the results of collaborative research between open textbook provider OpenStax College (OSC) and the OER Research Hub (OERRH), a Hewlett funded mixed methods open research project examining the impact of open educational resources (OER) on learning and teaching. The paper focuses primarily on the results of two surveys that were conducted with educators using a range of OSC open textbooks during 2013 and 2014/2015. The results of this research shows that OER such as OSC enables a majority of educators to better respond to student needs whilst often making teaching easier and in some instances changing teaching practices. Although this paper does not focus on the impact of OER on students, a majority of educators surveyed perceive an increase in student satisfaction when using OER such as OSC and believe that OSC are saving students money.